2022
DOI: 10.1038/s41598-022-11172-1
|View full text |Cite
|
Sign up to set email alerts
|

Daily blood pressure profile and blood–brain barrier permeability in patients with cerebral small vessel disease

Abstract: Cerebral small vessel disease (CSVD) plays an important role in cognitive impairment, stroke, disability, and death. Hypertension is the main risk factor for CSVD. The use of antihypertensive therapy has not resulted in the expected decrease in CSVD complications, which may be related to the underestimation of significance of daily blood pressure profile for blood–brain barrier (BBB) permeability. 53 patients with CSVD of varying severity (mean age 60.08 ± 6.8 years, 69.8% women, subjects with treated long-sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…A large area of necrosis can be seen in the left hemisphere, including the presence of neuro brillary tangles and amyloid plaques in the hippocampus and frequent amyloid plaques in the cerebral cortex, thickening of arterial walls, perivascular spaces are also found Enlargement, arteriosclerosis, microbleeds, and white matter thinning are consistent with features of CSVD and underscore the importance of the gut-vagus-brain axis in late-onset post-stroke dementia(Jiaerken et al, 2021). Furthermore, age-and hypertension-related cerebral small vessel disease are also major determinants of cognitive decline and disability in the elderly(Dobrynina et al, 2022;Goldstein et al, 2022).At present, treatment measures are mainly based on the characteristics of risk factors, the type and severity of biomarkers, and the severity of clinical sequelae. In clinical practice, blood pressure lowering, thrombolysis, and antiplatelet therapy are mostly used(Arba et al, 2019;Pan et al, 2022;Du H et al, 2022).…”
mentioning
confidence: 86%
“…A large area of necrosis can be seen in the left hemisphere, including the presence of neuro brillary tangles and amyloid plaques in the hippocampus and frequent amyloid plaques in the cerebral cortex, thickening of arterial walls, perivascular spaces are also found Enlargement, arteriosclerosis, microbleeds, and white matter thinning are consistent with features of CSVD and underscore the importance of the gut-vagus-brain axis in late-onset post-stroke dementia(Jiaerken et al, 2021). Furthermore, age-and hypertension-related cerebral small vessel disease are also major determinants of cognitive decline and disability in the elderly(Dobrynina et al, 2022;Goldstein et al, 2022).At present, treatment measures are mainly based on the characteristics of risk factors, the type and severity of biomarkers, and the severity of clinical sequelae. In clinical practice, blood pressure lowering, thrombolysis, and antiplatelet therapy are mostly used(Arba et al, 2019;Pan et al, 2022;Du H et al, 2022).…”
mentioning
confidence: 86%
“…54,55 In humans, BBB breakdown is an early biomarker of cognitive impairment, 56 specifically BBB breakdown in the hippocampus worsened mild cognitive impairment. 57 Although BBB disruption is present in some patients with hypertension 58 and may be associated with changes in daily blood pressure profile, 59 it has not been widely reported as a key feature of hypertension. Whether this is a result of the difficulty to evaluate the effect of hypertension in the presence of other comorbidities, or a true indication of the low prevalence of BBB disruption in the human patient population remains to be determined.…”
Section: Neurovascular Unit Dysfunctionmentioning
confidence: 99%
“…71 The BBB permeability parameters from DCE MRI have been found to correlate to ambulatory blood pressure measures in healthy subjects and cSVD patients with antihypertensive therapy. 72 Studies on patients with MCI found no relation between cardiovascular risk factors and BBB disruption. 73,74 The effect of cardiovascular risk factors on the water exchange rate measured by ASL is somewhat controversial.…”
Section: Bbb Disruption In Ageing and Cardiovascularmentioning
confidence: 99%
“…15 Hypertension and increased arterial blood pulsatility are considered to cause BBB impairment by inducing extreme forces on the endothelial cells and tight junctions (mechanotransduction), thereby damaging the physical BBB. 72 Meanwhile, the increased blood pulsatility in hypertension may also cause enlargement of the arterial PVS by damaging the surrounding tissue and by increasing vessel tortuosity. 95 Age is the other common underlying risk factor that is related to both BBB disruption 70,71 and enlargement of PVS.…”
Section: Insights From Clinical Studies On Bbb Disruptionmentioning
confidence: 99%